De volta para o passado? : uma análise crítica de reproposição das "Santas Missões Populares" no século xxi - Souza, Valdemir de França (2011)
Our study aims to show how such a method, which emerged in the modern age, once adapted to current circumstances and making use of new communication technologies, is being encouraged again by the Catholic Church as an alternative in the recovery of traditions and social and religious values lost in the last decades, mainly aiming to prevent the migration of believers to other churches and to the so-called new religious movements . For this, we will analyze the documentation produced by the Regional churches in search of the justifications used for their recovery, and their real interests, linked, as we assume, the pursuit of conquest / maintenance of Catholic religious hegemony in the society of Eastern Northeast Brazil. Hegemony is undermined in successive decades of the Catholic aggiornamento implemented after the Second Vatican Council (1962-1965), both for ad intra processes such as disorientation and loss of landmarks due to changes in the Catholic imagination, and for ad extra, as a result of secularization, migration, urbanization within states and penetration, more aggressive, churches and religious movements competing with the proposed Catholic.